Kerygmat a wydarzenie w głoszeniu cudów Jezusa - Twardy, Jan (Śląskie Studia Historyczno-Teologiczne, 2006)
Contemporary homilets of German language area are vividly interested in a message and historical nature of evangelical description of miracles.Like in the Gospels whose character is of historical-kerygmatic nature – similarly in description of Jesus miracles they are closely united and create both the event and the meaning element.In the apostolic preaching the theological interpretation of miracles has been united with their existence and narration. To explain the listeners the contents of miracles in the best way, the preacher ought to distinguish in them a literary form, a kerygmat and an event. If the preacher wants the kerygmat to be understood and still actual, he is obliged to accentuate historicity of miracles of Jesus. In this way, the preacher will be able to act against the tendencies of lay and liberal specialists in religious studies who undermine historicity of the Gospel – also description of miracles.Therefore, looking properly at evangelical description of miracles – and through them – the preacher will be able to bring closer to us the redemptive wonders of Christ who „is just miracle of all miracles” (Alfred Läpple).